Situation Report: Romania, 11 July 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Coverage of Speeches at the Helsinki Conference The Situation of the Theater Reviewed Number of Industrial Centrals Reduced Foreign Economic Relations Naval Commander Dies CC Decision on the Increased Role of Women in Society